The Gut Viral Metagenome Analysis of Domestic Dogs Captures Snapshot of Viral Diversity and Potential Risk of Coronavirus - Shi, Ying; Tao, Jie; Li, Benqiang; Shen, Xiaohui; Cheng, Jinghua; Liu, Huili (Frontiers in Veterinary Science, 2021)
The close relations between dogs (Canis lupus familiaris) and humans lay a foundation for cross species transmissions of viruses. The co-existence of multiplex viruses in the host accelerate viral variations. For effective prediction and prevention of potential epidemic or even pandemic, the metagenomics method was used to investigate the gut virome status of 45 domestic healthy dogs which have extensive contact with human beings. A total of 248.6 GB data (505, 203, 006 valid reads, 150 bp in length) were generated and 325, 339 contigs, which were best matched with viral genes, were assembled from 46, 832, 838 reads. In the aggregate, 9,834 contigs (3.02%) were confirmed for viruses. The top 30 contigs with the most reads abundance were mapped to DNA virus families Circoviridae, Parvoviridae and Herpesviridae; and RNA virus families Astroviridae, Coronaviridae and Picornaviridae, respectively. Numerous sequences were assigned to animal virus families of Astroviridae, Coronaviridae, Circoviridae, etc.; and phage families of Microviridae, Siphoviridae, Ackermannviridae, Podoviridae, Myoviridae and the unclassified phages. Further, several sequences were homologous with the insect and plant viruses, which reflects the diet and habitation of dogs. Significantly, canine coronavirus was uniquely identified in all the samples with high abundance, and the phylogenetic analysis therefore showed close relationship with the human coronavirus strain 229E and NL63, indicating the potential risk of canine coronavirus to infect humans by obtaining the ability of cross-species transmission. This study emphasizes the high detection frequency of virus harbored in the enteric tract of healthy contacted animal, and expands the knowledge of the viral diversity and the spectrum for further disease-association studies, which is meaningful for elucidating the epidemiological and biological role of companion animals in public health.